María Cecilia Hang Pueblos originarios y Ley de Servicios de Comunicación Audiovisual: El caso Wall Kintun TV - Hang, María Cecilia (Facultad de Periodismo y Comunicación Social, 2019)
The paper analyzes the recognition of indigenous peoples’ right to identity in their role as audiovisual communication services’ providers from analyzing the case of Wall Kintun TV, the first mapuche television channel, in the context of the creation and introduction of the Audiovisual Communication Services Act (LSCA) as a result of the process of recovery of the Latin American critical tradition.